The impact of embedded global innovation networks on manufacturing value chains - Min Zhang; Long Wei; Ziyu Yi (Scientific Reports)
Abstract Against the backdrop of in-depth globalization, global innovation collaboration has emerged as a crucial methodology for countries to break through boundaries in innovation and secure technological gains. Governments of various countries (regions) have regarded global innovation collaboration as a strategic priority increasingly, seeking global scale resources and enthusiastically participating in global innovation networks (GINs). This study characterizes the structural features of GINs and examines their positive impact on the Global Value Chain (GVC). Specific reference is made to manufacturing industries. The results demonstrate that both the embedding breadth and the embedding depth of GINs significantly enhance the GVC position in manufacturing industries. Furthermore, the results show developed economies exhibit a pronounced improvement in manufacturing GVC positions, while developing economies face persistent risks like “low-end lock-in”. To further investigate the heterogeneous effects of GINs embeddedness on developed and developing economies, this study introduces a new interaction term between intellectual property rights (IPR) protection and GINs embeddedness. The results reveal that strengthened IPR protection enhances the manufacturing GVC position in developed economies significantly, while it suppresses the manufacturing GVC upgrading in developing economies. These findings contribute to the theoretical understanding of GINs’ impact and provide actionable insights for developing economies to design innovation collaboration strategies.